(S)-5′-C-Aminopropyl-2′-O-methyl nucleosides enhance antisense activity in cultured cells and binding affinity to complementary single-stranded RNA. (15th January 2021) - Kajino, Ryohei; Ueno, Yoshihito
Graphical abstract: Abstract: Antisense oligonucleotides (ASOs) are a promising clinical tool that could be applied for unmet medical needs, but there are several limitations for their therapeutic application. Here, we designed and synthesized ( S )-5′- C -aminopropyl-2′- O -methylcytidine, and oligonucleotides containing ( S )-5′- C -aminopropyl-2′- O -methyluridine and -methylcytidine. We then investigated the properties of ASOs containing these nucleoside analogs. ( S )-5′- C -Aminopropyl modifications enhanced the thermal stability of DNA/RNA duplexes when compared to other commercially available 2′- O -methyl modifications. This suggested that the terminal ammonium cation on the alkyl side chains neutralized the negative charge of the phosphates in the duplex. Additionally, the overall conformation of ASO/RNA duplexes was retained with the modified ASOs. Thus, these duplexes exhibited the ability to elicit RNase H activity. Furthermore, we found that ASOs containing the ( S )-5′- C -aminopropyl modification exhibited higher antisense potency than those containing the 2′- O -methyl modification in cultured cells. Therefore, the ( S )-5′- C -aminopropyl-2′- O -methyl nucleosides synthesized in this study are promising candidates for developing antisense therapeutics.